PENGARUH TINGKAT KEMATANGAN BUAH TERHADAP PERKECAMBAHAN BIJI PADA Pyracantha spp. - Surya, Muhammad Imam (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2009)
A research was conducted to study the effect of fruit maturity on seed germination capacity of four Pyracantha species, i.e. P. koidzumi, P. angustifolia, P. crenato-serrato and P. fortunea. The fruits were collected from Cibodas Botanic Garden in two different states of fruit maturity, namely physiological maturity and harvest maturity. In general, seeds of Pyracantha spp. were starting to germinate epigeally in 5 â 14 days after sowing and the states of fruit maturity influenced seed germination capacities. In P. angustifolia and P. crenato-serrato, seed germination capacities were better if the seeds were extracted from brightly colored mature fruit (physiological maturity). Meanwhile, in P. fortune and P. koidzumi, better germination capacities were obtained in seeds extracted from dark collored drying mature fruit (harvest maturity).